Pembuatan Alat Tracking Artefak pada Museum Menggunakan Modul GSM Berbasis Mikrokontroler dan Short Message Service - Irzan Marza (JITCE (Journal of Information Technology and Computer Engineering), 2019)
The museum is in charge of providing facilities for these research activities for anyone, in addition to the museum in charge of carrying out the research activities themselves and disseminating the results of the research to the development of general science. However, in reality there is still the fact that cases of missing historical objects have a value of up to millions of rupiah. This study aims to create a tracking system that is able to track artifacts in the museum using the BTS system. Therefore, the author will make a tool that can track the position of the artifact with the Tracking method. The design of the study that the author will adopt from the above problem is "Making an Artifact Tracking Tool at the Museum Using a Microcontroller and Short Message Service-Based GSM Module".